Climate Change in Pakistan and its Resilience Efforts - Dr. Najaf Ali; Altaf Majeed; Shumaila Saeed; Nimra Zulfiqar; Muhammad Javed Ashraf 3 (Al-Qanṭara, 2023)
Climate change poses a critical and growing threat to Pakistan, with adverse impacts already marked across various sectors of the country's economy and environment. This paper explores the multidimensional challenges of climate change in Pakistan and examines the nation's resilience efforts in response to these challenges. Pakistan's geographical diversity, from the Himalayan and Karakoram mountain ranges to the vast plains and coastal regions, makes it particularly vulnerable to climate change-induced disasters, including extreme weather events, glacial melt, and rising temperatures. These changes have far-reaching consequences for agriculture, water resources, public health, and overall socio-economic stability. Pakistan has taken substantial steps to enhance its climate resilience in response to these challenges. The paper highlights key initiatives, such as the National Climate Change Policy and the Ten Billion Tree Tsunami Program, which reflect the country's commitment to mitigating and adapting to climate change. Despite these efforts, Pakistan faces ongoing challenges, including resource constraints and the need for improved coordination among various stakeholders.